Analysis of Mathematical Connection Ability in Minimum Competency Assessment Algebra Test Viewed From Students’ Intrapersonal and Interpersonal Intelligence - Fitri Salsabila Ayu Andriani; Siti Inganah; Arif Hidayatul Khusna (AL-ISHLAH: Jurnal Pendidikan, 2024)
Mathematical connection is a crucial skill for students, as it reduces the need to memorize numerous concepts and procedures independently. This study explores the variance in mathematical connection abilities among students with different intelligence types, specifically intrapersonal and interpersonal, in the context of solving algebraic problems on the AKM (Minimum Competency Assessment) test. Utilizing a qualitative descriptive methodology, this research focused on four students from class VIII-B at an Islamic Junior High School in Blitar. Data were gathered through questionnaires assessing intrapersonal and interpersonal intelligence, followed by the AKM Algebra test and interviews with selected students—two from each intelligence category. The findings reveal that students with interpersonal intelligence demonstrated superior mathematical connection abilities compared to their intrapersonal counterparts. Individuals with interpersonal intelligence met all indicators of mathematical connections, whereas intrapersonal intelligence subjects varied, with some meeting only one or two. This discrepancy underscores that students of the same intelligence type can exhibit differing levels of mathematical connection abilities, influenced by various factors such as mathematical skills, development of geometric thinking, and reasoning abilities.